Actualización diagnóstica y terapéutica de la enterocolitis necrotizante en neonatos (Revisión bibliográfica) - Vallejo Vallejo, Zoila Rosa (2023)
ABSTRACT: Background: Necrotizing enterocolitis in neonates is a gastrointestinal emergency with a high morbimortality rate due to its complex and late diagnosis because of its rapid and progressive evolution; characterized by necrotic-ischemic lesion of the intestinal mucosa, a product of inflammation in response to multiple factors, prematurity being the main one. Early diagnosis and timely treatment reduce the risk of intestinal perforation and the need for surgery, avoiding complications. Objective: To propose an algorithm applicable in the different levels of health care for early diagnosis by describing the clinical manifestations, laboratory, and imaging tests; and to establish a timely therapeutic method according to the need and general condition of the patient through an updated bibliographic review. Method: It is a descriptive, retrospective, cross-sectional literature review of 40 scientific articles obtained from databases such as PubMed, and Science Direct, among others, employing the PRISMA statement together with the DeCS/MeSH published in the last five years. Results: the proposed algorithm can be applied in the different levels of health care, starting with the prevention and promotion of necrotizing enterocolitis by identifying antecedents and risk factors; to subsequently by listing the clinical manifestations and by describing the results of laboratory and imaging tests the early diagnosis is reached; finally by staging said pathology based on Bell's criteria the appropriate therapeutic measures can be established in each case. Conclusions: Knowing the history, risk factors, clinical manifestations, and radiological signs allows an early diagnosis, and through its staging based on the BELL criteria, the prognosis can be assessed, and timely treatment can be established according to the need and general clinical condition of the patient decreasing the risk of morbimortality, late diagnosis, need for surgery, possible complications and poor prognosis. Keywords: neonatal necrotizing enterocolitis, diagnosis, treatment.